Evaluating the accuracy and quality of an iPad Pro's built-in lidar for 3D indoor mapping - Tee-Ann Teo; Chen-Chia Yang (Developments in the Built Environment, 2023)
This study aimed to assess the accuracy of the lidar sensor on an iPad Pro and its potential for creating 3D BIM. Data was collected through different scanning methods in various environmental conditions. The results showed that the iPad Pro's lidar sensor produced accurate point clouds in static acquisition experiments with point distances of less than 1 mm from their best-fitting plane. However, in dynamic acquisition experiments, the distance increased to an average of 1 cm due to changes in the iPad Pro's pose. The study also found that the accuracy of the registered point clouds was better when scanning smaller areas with limited pose changes. Based on the findings, the study recommends maintaining a distance of 1–1.5 m between the iPad Pro and the target, as the target's color has minimal impact on scanning accuracy. Avoiding large posture changes while scanning can improve the accuracy of the point clouds in scan-to-BIM projects.